Post-Release Substance Abuse Outcomes Among HIV-Infected Jail Detainees: Results from a Multisite Study. - Krishnan, Archana; Wickersham, Jeffrey A; Chitsaz, Ehsan; Springer, Sandra A; Jordan, Alison O; Zaller, Nick; Altice, Frederick L (AIDS and behavior, 2012)
HIV-infected individuals with substance use disorders have a high prevalence of medical and psychiatric morbidities that complicate treatment. Incarceration further disrupts healthcare access and utilization. Without appropriate diagnosis and treatment, drug relapse upon release exceeds 85 %, which contributes to poor health outcomes. A prospective cohort of 1,032 HIV-infected jail detainees were surveyed in a ten-site demonstration project during incarceration and six-months post-release, in order to examine the effect of predisposing factors, enabling resources and need factors on their subsequent drug use. Homelessness, pre-incarceration cocaine and opioid use, and high drug and alcohol severity were significantly associated with cocaine and opioid relapse. Substance abuse treatment, though poorly defined, did not influence post-release cocaine and opioid use. An approach that integrates multiple services, simultaneously using evidence-based substance abuse, psychiatric care, and social services is needed to improve healthcare outcomes for HIV-infected persons transitioning from jails to the community.